Compact genetic algorithm of window size’s selection for time series prediction in neural networks - Волченко, Е. В. (Problems of Informatization and Control, 2011)
The problem of data preprocessing for time series prediction using multilayer neural networks is considered. A compact genetic algorithm for determining the size of windows to build a training set is proposed. A method of encoding chromosomes is described. Fitness-function and ways to stop the genetic algorithm is developed. A numerical comparison ofprediction results of different types of time series with known methods and neural network prediction using the developed algorithm is shown